SITRONELAL CYCLE-HYDROGENATION TANDEM CREATED ZrO MONTMORILLONIT WITH VARIATION METHOD REACTION - Is Fatimah; Septian Perwira Yudha; Dwiarso Rubiyanto; Thorikul Huda (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2013)
Tandem cyclization reaction towards menthol-citronellal hydrogenation reactions through one-step reaction with a variety of methods using pillared montmorillonite catalyst ZrO2 (Zr-MMT) have been done. The research aimed to determine the effectiveness of Zr-MMT catalyst in the reaction process with two different methods; first method comprises reacting flow system to citronellal - catalyst mixture after reflux with pressure and flow H2 of 3 kPa, and the other method consists of a flow system to the citronellal -catalyst mixture at the temperature of 200o C with H2 flow pressure of 2 kPa. Reaction products were analyzed using GC-MS to determine the total conversion and product yield of menthol. The results showed that the different methods give different reaction mechanisms significantly. The first method gives almost to 99% conversion of citronellal with major products of isomenthone and isopulegol while the second method give the conversion of 5.18% with 0.39% selectivity to menthol products. Compared with natural montmorillonite, both processes showed higher conversion in which the conversion of citronellal over montmorillonite give the concersion less than 5%. The adequacy of H2 flow rate as a reactant is an important factor affection the mechanism is discussed in this paper.